New Porphyrin/Fe-Loaded TiO2 Composites as Heterogeneous Photo-Fenton Catalysts for the Efficient Degradation of 4-Nitrophenol. (17th January 2013) - Mele, Giuseppe; Pio, Iolanda; Scarlino, Anna; Bloise, Ermelinda; Del Sole, Roberta; Palmisano, Leonardo; Vasapollo, Giuseppe
Abstract : A new class of porphyrin(Pp)/Fe co-loaded TiO2 composites opportunely prepared by impregnation of [5, 10, 15, 20-tetra(4- tert -butylphenyl)] porphyrin (H2 Pp) or Cu(II)[5, 10, 15, 20-tetra(4- tert -butylphenyl)] porphyrin (CuPp) onto Fe-loaded TiO2 particles showed high activities by carrying out the degradation of 4-nitrophenol (4-NP) as probe reaction in aqueous suspension under heterogeneous photo-Fenton-like reactions by using UV-visible light. The combination of porphyrin-Fe-TiO2 in the presence of H2 O2 showed to be more efficient than the simple bare TiO2 or Fe-TiO2 .